2019
DOI: 10.3390/su11226210
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling Sustainable Homecare with Urban Transport and Different Skilled Nurses Using an Approximate Algorithm

Abstract: The essential characteristics that distinguish homecare services from other routing and scheduling problems are relatively few patients being spread out over a large urban area, long transport times and several different services being provided. The approach that the authors present herein was developed to solve planning homecare services according to the criterion of increasing social sustainability and incorporating environmentally sustainable transport systems. The objective of this paper is to present a to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For each category, we have sub-categories (Route, Staff Members, Patients) and the columns of tables 6 and 7 show the criteria appearing at least three times. The research conducted on articles published after May 2019 showed that sustainability is getting more attention lately (Ros-McDonnell et al, 2019;Quintanilla et al, 2020). In (Cinar et al, 2019), a new criterion is studied: they maximize the global priority of the visited patients, who are ranked depending on then their condition, their dependency and the last time they were visited.…”
Section: Proposed Approaches and Experimentationsmentioning
confidence: 99%
“…For each category, we have sub-categories (Route, Staff Members, Patients) and the columns of tables 6 and 7 show the criteria appearing at least three times. The research conducted on articles published after May 2019 showed that sustainability is getting more attention lately (Ros-McDonnell et al, 2019;Quintanilla et al, 2020). In (Cinar et al, 2019), a new criterion is studied: they maximize the global priority of the visited patients, who are ranked depending on then their condition, their dependency and the last time they were visited.…”
Section: Proposed Approaches and Experimentationsmentioning
confidence: 99%